Molecular chaperones at the host–virus interface: heat shock protein roles in HIV-1 and emerging insights for HIV-2 and dual infection - Arthur, Sabastine Eugene; Klogo, Kirk; Mensah, Emmanuel Kobina; Cudjoe, Maame Ama Pentsiwa; Mensah, Adomia Baaba; Ankrah, Nyamekye Amoabeng; Omosule, Catherine Laaripuoh; Bonney, Evelyn Yayra; Kyei, George Boateng (Frontiers in Cellular and Infection Microbiology, 2025)
Heat shock proteins (HSPs) are essential molecular chaperones involved in protein folding, cellular stress responses, and homeostasis. Recent studies reveal their critical and dual roles in the human immunodeficiency virus (HIV) life cycle, both promoting and restricting viral replication, latency, and immune modulation. This review synthesizes current evidence on how key HSP families, HSP70, HSP90, and HSP40, interact with HIV proteins such as Tat, Rev, Nef, and Vpx, affecting viral transcription, protein trafficking, and latency. We also highlight Heat Shock Factor 1 (HSF1) as a direct regulator of the HIV-1 long terminal repeat (LTR), facilitating latency reversal via recruitment of transcriptional co-activators like p300 and P-TEFb. In HIV-2, distinct HSP-mediated mechanisms, such as HSP40-facilitated nuclear import of Vpx-associated pre-integration complexes, may contribute to its lower replication rates and deeper latency. The review further discusses the incorporation of HSPs into virions, their potential as therapeutic targets, including HSP90 inhibitors and HSF1 modulators, and identifies gaps in understanding HSP roles in HIV-2 and dual infections. We propose future research directions that could harness host stress-response machinery to address HIV persistence and latency.